Little Fire Ant Wasmannia auropunctata (Roger) (Insecta: Hymenoptera: Formicidae) - Virginia Rose Seagal; Andrea Lucky (EDIS)
The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences.